Comparing the Performance of Microsatellites and RADseq in Population Genetic Studies: Analysis of Data for Pike (Esox lucius) and a Synthesis of Previous Studies - Sunde, Johanna; Yıldırım, Yeşerin; Tibblin, Petter; Forsman, Anders (Frontiers in Genetics, 2020)
Population genetic studies reveal biodiversity patterns and inform about drivers of evolutionary differentiation and adaptation, including gene flow, drift and selection. This can advance our understanding and aid decision making regarding management and conservation efforts. Microsatellites have long been used in population genetic studies. Thanks to the development of newer techniques, sequencing approaches such as restriction site associated DNA sequencing (RADseq) are on their way to replace microsatellites. However, the performance of these two marker types in population genetics have rarely been systematically compared. We utilized three neutrally and adaptively differentiated populations of anadromous pike (Esox lucius) to assess the relative performance of microsatellites and RADseq. First, both methods were used to genotype the same set of individuals (N = 64). Next, RADseq genotyping was performed on a subset of the individuals (N = 30) to assess effects of sample size. Comparisons of estimated genetic diversity and structure showed that both markers uncovered genetic structuring, and that RADseq provided higher resolution, even for the smaller sample size. A search for outlier loci performed on the SNP dataset pointed to signs of selection associated with salinity and temperature, exemplifying the utility of RADseq to inform about the importance of different environmental factors. Lastly, the results of earlier studies that have investigated population structure using both marker types were synthesized. The findings in the present study were largely consistent with previous studies, together indicating that, due to the higher number of loci commonly obtained with RADseq compared to microsatellites, it allows for a clearer detection of higher resolution of genetic structure, even when fewer individuals are used for RADseq.